Preferential phosphatidylinositol 5-phosphate binding contributes to a destabilization of the VHS domain structure of Tom1 - Xiong, Wen (Sci Rep, 2019)
Tom1 transports endosomal ubiquitinated proteins that are targeted for degradation in the lysosomal pathway. Infection of eukaryotic cells by Shigella flexneri boosts oxygen consumption and promotes the synthesis of phosphatidylinositol-5-phosphate (PtdIns5P), which triggers Tom1 translocation to signaling endosomes. Removing Tom1 from its cargo trafficking function hinders protein degradation in the host and, simultaneously, enables bacterial survival. Tom1 preferentially binds PtdIns5P via its VHS domain, but the effects of a reducing environment as well as PtdIns5P on the domain structure and function are unknown. Thermal denaturation studies demonstrate that, under reducing conditions, the monomeric Tom1 VHS domain switches from a three-state to a two-state transition behavior. PtdIns5P reduced thermostability, interhelical contacts, and conformational compaction of Tom1 VHS, suggesting that the phosphoinositide destabilizes the protein domain. Destabilization of Tom1 VHS structure was also observed with other phospholipids. Isothermal calorimetry data analysis indicates that, unlike ubiquitin, Tom1 VHS endothermically binds to PtdIns5P through two noncooperative binding sites, with its acyl chains playing a relevant role in the interaction. Altogether, these findings provide mechanistic insights about the recognition of PtdIns5P by the VHS domain that may explain how Tom1, when in a different VHS domain conformational state, interacts with downstream effectors under S. flexneri infection.